Antibody durability at 1 year after Sputnik V vaccination - Sanchez, Lautaro Nicolas (2022)
Antibody waning against SARS-CoV-2 over time after vaccination, together with the emergence of new viral variants, pose great challenges for ending the pandemic. To our knowledge, no previous work has assessed the long-term prevalence of anti-SARS-CoV-2 antibodies in individuals vaccinated with Sputnik V (Gam-COVID-Vac).1 We assessed the persistence of anti-spike IgG antibodies and their neutralising capacity against the original SARS-CoV-2 lineage (B.1) and a local isolate of the BA.1 lineage of the omicron (B.1.1.529) variant in a longitudinal cohort during 1 year after Sputnik V vaccination in Argentina. We used 400 paired serum samples (100 samples at each timepoint, including at baseline before vaccination) from 100 volunteers who received two doses of Sputnik V that were obtained between Jan 1, 2021, and Jan 15, 2022. Participants with current or previous SARS-CoV-2 infection, determined by assessing seropositivity to nucleocapsid protein, were excluded from the analysis. The geometric mean (GM) of international units of IgG anti-spike antibodies2 per mL (IU/mL) were 994 (95% CI 769–1285) at 42 days, 80 (60–106) at 180 days, and 36 (27–47) at 360 days after completion of the two-dose vaccination scheme (figure A; appendix p 2). Overall, a 27-fold reduction in IgG was observed 1 year after Sputnik V vaccination.